A política externa em direitos humanos no governo Lula (2003-2010) - Neves, Arthur Volpon [UNESP] (2014)
This study aims to examine the human rights foreign policy of the Lula government. This is done through three chapters, including an introduction and a conclusion. The first chapter analyzes the normativity of the international human rights regime and its historical evolution. The second chapter discusses the role of the constructivist approach on foreign policy analysis through research on agent-structure and the role of identities and ideas. Human rights are correlated with the development issue and the paradigms of the Brazilian foreign policy. The last chapter addresses the human rights debate in Brazilian foreign policy of the Lula government, and different approaches that interpret such policy serve as a logical structure to discuss the issues of human rights, development and autonomy.